2019
DOI: 10.31486/toj.18.0144
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Grit and Resilience in Emergency Medical Service Personnel

Abstract: Background: Emergency medical service (EMS) personnel are regularly exposed to traumatic incidents and experience higher rates of symptoms of posttraumatic stress disorder (PTSD) than the general population. Grit is a construct proposed to be associated with achievement, but it has demonstrated preliminary evidence of an association with resilience. The current study examined the relationship between grit and resilience among EMS workers. Methods: A link to an online survey was sent to East Baton Rouge Parish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
2
24
0
1
Order By: Relevance
“… 15 , 16 Research on the relationship between grit and resilience in emergency medical service (EMS) workers has also shown that grit is associated with lower PTSD symptoms, and while associated with factors of resilience (i.e., coping mechanisms), grit appears to be a distinct construct. 17 Given the potential of frontline healthcare workers to experience significant stress during the COVID-19 pandemic, it is important to consider how resilience and grit may safeguard against these negative psychological factors.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 Research on the relationship between grit and resilience in emergency medical service (EMS) workers has also shown that grit is associated with lower PTSD symptoms, and while associated with factors of resilience (i.e., coping mechanisms), grit appears to be a distinct construct. 17 Given the potential of frontline healthcare workers to experience significant stress during the COVID-19 pandemic, it is important to consider how resilience and grit may safeguard against these negative psychological factors.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, high resilience scores were uncovered in staff working in the context of emergency services. The ability to overcome adverse situations, adapt to them, and come out stronger the other end, was greater in individuals with stressful occupations as they require emotional management skills to carry out their work [ 21 , 22 , 24 , 25 ]. Studies have not only been performed directed towards this population; in fact, research has also been developed at a community level in relation to resilience in hospitals, given the importance of resilience when delivering quality care to service users [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, this skill is currently a hot topic of study in health workers and those working in emergency services because of the arduous work they perform and the stress it entails [ 21 , 22 , 23 , 24 , 25 ]. Studies carried out with patients with different pathologies at different stages of the disease process are also highly relevant, especially those conducted with oncology patients [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Además, es una herramienta útil para la realización de encuestas a profesionales de distintos ámbitos, como la medicina y la salud (Ferguson et al, 2016;Iskander et al, 2017;Stanley et al, 2017;Holroyd y Edyvean, 2018;Bogetz et al, 2019;Musso et al, 2019;Peultier et al, 2019;DeBiasi et al, 2020;Grossman et al, 2020;Moran y Davis, 2020), la educación (Bolliger y Martin, 2018), o las bibliotecas (Kim, Geary y Bielefield, 2018;Reed, 2017;Williamson, 2017).…”
Section: Introductionunclassified